Use of social media for surgical education in Australia and New Zealand. Issue 6 (27th February 2020) - Larkins, Kirsten; Murphy, Victoria; Loveday, Benjamin P. T.
Abstract: Background: Social media are an increasingly important tool for educators, although their use for surgical education in Australia and New Zealand (ANZ) has not been quantified. This study aimed to determine the social media presence of surgical training institutions in ANZ, quantify the proportion of their social media content that is educational, compare engagement between educational and non‐educational content, and determine perspectives on using social media for education. Methods: An online search was conducted in October 2018 to determine the social media presence of surgical training institutions accredited to deliver under‐ and post‐graduate surgical education in ANZ. All their posts on Facebook and Twitter from November 2017 to October 2018 were categorized as educational or non‐educational. Engagement on Twitter was analysed using retweets. An online survey was distributed to each institution to investigate their social media strategy and opinions on the use of social media for surgical education. Results: Seven out of 37 (19%) surgical training institutions had active social media accounts. Educational content accounted for 677/4615 (14.7%) of their posts. Educational content was retweeted more often than non‐educational content (17.2 versus 5.4, P = 0.002). Seven out of 37 (19%) institutions responded to the survey, with one respondent having a policy for and utilising social media for surgical education. Conclusions: Social media are being used by a minority of surgical training institutions for educational purposes in ANZ. Social media content is primarily non‐educational although educational posts attract more engagement. Further research is required to assess the efficacy of surgical education on social media. Abstract : Investigation into the use of social media platforms by surgical training institutions in Australia and New Zealand. This study explores the use of social media, types of content posted, engagement with social media posts and perspectives towards use of social media for surgical education.